Ch.2 Solving General Linear Systems

Return to TOC


Techniques of Proofs

Induction: Prove for the first case, prove that if true for some case, must be true for next case
First case is base step
Next step is the inductive step, assume the inductive hypothesis (works up to some kk) holds.

Example 2.1

Show that 1+2+3++n=n(n+1)21+2+3+\cdots+n=\frac{n(n+1)}{2}


We first show the base step. When n=1n=1, 1=1(2)2=11=\frac{1(2)}{2}=1, so the statement holds.
Suppose 1+2++k=k(k+1)21+2+\cdots+k=\frac{k(k+1)}{2} (inductive hypothesis). Then
1+2++k+k+1=k(k+1)2+k+1=k(k+1)+2(k+1)2=k2+3k+22=(k+1)(k+2)2=(k+1)(k+1+1)21+2+\cdots+k+k+1=\frac{k(k+1)}{2}+k+1=\frac{k(k+1)+2(k+1)}{2}=\frac{k^2+3k+2}{2}=\frac{(k+1)(k+2)}{2}=\frac{(k+1)(k+1+1)}{2}Ttherefore it is also true. Thus, 1+2+3++n=n(n+1)21+2+3+\cdots+n=\frac{n(n+1)}{2} for all natural numbers nn. _\blacksquare

Contradiction: show something is false to prove that the opposite must be true
Assume the opposite, show how that leads to a contradiction, then conclude that the original assumption must be false, so the opposite is true.

Example 2.2

Prove there are infinitely many primes


Suppose there are a finitely many primes p1,p2,...,pkp_1,p_2,...,p_k. Consider the number p1p2...pk+1p_1p_2...p_k+1. None of the primes divide this number, as it leaves a remainder of 1, however, every number is the product of primes. That is a contradiction, meaning that the initial proposition that there are finitely many primes must be false. Therefore, there must be infinitely many primes. _\blacksquare


Logic Operators and Set Notation

Use the following symbols for logic expressions and the respective set notation

def.logicset
or\lor\cup
and\land\cap
not¬\lnotAcA^c

Proofs can be conducted with logical operators or using truth tables

Example 2.3
PPQQPQP\lor QPQP\land Q¬P\lnot P¬(PQ)\lnot(P\lor Q)(¬P)(¬Q)(\lnot P)\land(\lnot Q)
TTTTFFF
TFTFFFF
FTTFTFF
FFFFTTT
Example 2.4

Show that ¬(PQ)¬P¬Q\lnot(P\lor Q)\equiv\lnot P\land \lnot Q


The left is true if both PP and QQ are false. The right is true is PP is false and QQ is false. Clearly, they are equivalent.


Show that ¬(PQ)=¬P¬Q\lnot(P\land Q)=\lnot P \lor \lnot Q


¬(PQ)=¬(¬(¬P¬Q))=¬¬(¬P¬Q)=¬P¬Q\lnot(P\land Q)=\lnot(\lnot(\lnot P\lor\lnot Q))=\lnot\lnot(\lnot P\lor\lnot Q)=\lnot P\lor\lnot Q

The expression PQP\implies Q (PP implies QQ) can be expressed as a truth table as follows

PPQQPQP\implies Q
TTT
TFF
FTT
FFT

If PP is true, then QQ is implied to be true, so QQ cannot be false.
If PP is false, then QQ could be either true or false.
So, PQ¬PQP\implies Q\equiv \lnot P\lor Q

Contrapositive: to prove PQP\implies Q, instead prove the equivalent ¬Q¬P\lnot Q\implies \lnot P

Proof Show that PQ¬Q¬PP\implies Q\equiv \lnot Q\implies \lnot P

PQ¬PQQ¬P¬(¬Q)¬P¬Q¬PP\implies Q\equiv\lnot P\lor Q\equiv Q\lor\lnot P\equiv\lnot(\lnot Q)\lor \lnot P\equiv\lnot Q\implies \lnot P

Similarly, PQP\iff Q (if and only if) is expressed

PPQQPQP\iff Q
TTT
TFF
FTF
FFT

and proven when
(PQQP)(P\implies Q\land Q\implies P) or
(PQ¬P¬Q)(P\implies Q\land \lnot P\implies\lnot Q) or
(PQ)(¬P¬Q)(P\land Q)\lor (\lnot P\land \lnot Q)

Logic operators are interchangeable with set notation:

(AB)C(AC)(BC)(AB)C=(AC)(BC)(A\lor B)\land C\equiv(A\land C)\lor(B\land C)\leftrightarrow (A\cup B)\cap C=(A\cap C)\cup(B\cap C)

Logic Proof

For the left hand side to be true, CC must be true, as well as either AA or BB. Looking at the right side, either ACA\land C or BCB\land C must be true. In either case, CC must be true. Then, if one of either AA or BB is true, one of those statements will be satisfied.

Set Proof

We must show (AB)C(AC)(BC)(A\cup B)\cap C\subseteq (A\cap C)\cup(B\cap C) and (AC)(BC)(AB)C(A\cap C)\cup(B\cap C)\subseteq (A\cup B)\cap C
For the first, suppose x(AB)Cx\in(A\cup B)\cap C. This means xCx\in C, and xAx\in A or xBx\in B. In other words, xCx\in C and xAx\in A, or xCx\in C and xBx\in B, which can be represented as (AC)(BC)(A\cap C)\cup(B\cap C), so (AB)C(AC)(BC)(A\cup B)\cap C\subseteq (A\cap C)\cup(B\cap C).
Next, suppose x(AC)(BC)x\in(A\cap C)\cup (B\cap C). Then xCx\in C regardless, and xAx\in A or xBx\in B, so xC(AB)x\in C\cap(A\cup B)
Since both sets are subsets of each other,
(aB)C=(AC)(BC)(a\cup B)\cap C=(A\cap C)\cup(B\cup C)


Homogeneous Linear Systems

Homogeneous linear systems have a constant of 00

Example solution set{z(2110)+w(0101)|z,wR}\left\{z\begin{pmatrix}-2\\1\\1\\0\end{pmatrix}+w\begin{pmatrix}0\\-1\\0\\1\end{pmatrix}\middle|z,w\in\mathbb{R}\right\}

Solution to a General Linear System

If a linear system has a particular solution p\vec{p} and its associated homogeneous system has a solution h\vec{h}, the solution set S={p+h}S=\{\vec{p}+\vec{h}\}

Proof

First show S{p+h}S\subseteq \{\vec{p}+\vec{h}\} set.
Take another solution vector sS\vec{s}\in S. Look at sp\vec{s}-\vec{p} and plug into the ii-th equation.
ai,1(s1p1)++ai,n(snpn)=didi=0a_{i,1}(s_1-p_1)+\cdots+a_{i,n}(s_n-p_n)=d_i-d_i=0
Therefore, sp=h\vec{s}-\vec{p}=\vec{h}, or s=p+h\vec{s}=\vec{p}+\vec{h}, meaning S{p+h}S\subseteq \{\vec{p}+\vec{h}\}.

Next show p+hS\vec{p}+\vec{h}\subseteq S.
Plugging into the ii-th equation,
ai,1(p1+h1)++ai,n(pn+hn)=di+0=dia_{i,1}(p_1+h_1)+\cdots+a_{i,n}(p_n+h_n)=d_i+0=d_i
Therefore, p+h\vec{p}+\vec{h} solves the system, so {p+h}S\{\vec{p}+\vec{h}\}\subseteq S.
Since each are subsets of each other, by the Principle of Extensionality, S={p+h}S=\{\vec{p}+\vec{h}\}.

Theorem: Every linear system has solutions of the form {p+h}={p+c1β1++ckβkc1,...,ckR}\{\vec{p}+\vec{h}\}=\{\vec{p}+c_1\vec{\beta}_1+\cdots+c_k\vec{\beta}_k|c_1,...,c_k\in\mathbb{R}\}

singular square matrix describes a homogeneous system of equation with infinitely many solutions
nonsingular square matrix describes a homogeneous system of equation with one solution

Example 2.5

A line in Rn\mathbb{R}^n can be represented by the set
L={p+tv  tR}L=\{\vec{p}+t\vec{v}\space|\space t\in\mathbb{R}\}
What is the set representation for the line going through (1,1,1)(1,1,1) and (2,3,4)(2,3,4) in R3\mathbb{R}^3?


The particular solution can be either of the two points. Choose (1,1,1)(1,1,1). The vector from (1,1,1)(1,1,1) to (2,3,4)(2,3,4) shows the direction, i.e. (1,2,3)(1,2,3)
The line is
L={(111)+t(123) | tR}L=\left\{\begin{pmatrix}1\\1\\1\end{pmatrix}+t\begin{pmatrix}1\\2\\3\end{pmatrix}\space\middle|\space t\in\mathbb{R}\right\}


What is the system for which this is the solution to?


Express this as
(xyz)=(111)+t(123)(x1y1z1)=t(123)\begin{pmatrix}x\\y\\z\end{pmatrix}=\begin{pmatrix}1\\1\\1\end{pmatrix}+t\begin{pmatrix}1\\2\\3\end{pmatrix}\rightarrow\begin{pmatrix}x-1\\y-1\\z-1\end{pmatrix}=t\begin{pmatrix}1\\2\\3\end{pmatrix}
We want to eliminate tt to get the system of equations. This can be done by row-reducing
(1x12y13z1)(1x10y12(x1)0z13(x1))\left(\begin{array}{c|c}1&x-1\\2&y-1\\3&z-1\end{array}\right)\sim\left(\begin{array}{c|c}1&x-1\\0&y-1-2(x-1)\\0&z-1-3(x-1)\end{array}\right)
The bottom two equations have no tt term, so those are used.
The system is
2x+y+1=03x+z+2=0  2xy=13xz=2\begin{matrix}-2x+y+1=0\\-3x+z+2=0\end{matrix}\space\longrightarrow\space\begin{matrix}2x-y=1\\3x-z=2\end{matrix}

Example 2.6

A plane in Rn\mathbb{R}^n can be represented by the set
P={p+tv+sw  t,sR}P=\{\vec{p}+t\vec{v}+s\vec{w}\space|\space t,s\in\mathbb{R}\}
Find the set for the plane going through (1,1,1)(1,1,1), (2,1,2)(2,1,2) and (1,1,3)(-1,-1,-3)


The particular solution can be any of these; choose p=(1,1,1)\vec{p}=(1,1,1)
The vector from (1,1,1)(1,1,1) to (2,1,2)(2,1,2) is (1,0,1)(1,0,1) and the vector from (1,1,1)(1,1,1) to (1,1,3)(-1,-1,-3) is (2,2,4)(-2,-2,-4), so the set is
P={(111)+t(101)+s(224) | t,sR}P=\left\{\begin{pmatrix}1\\1\\1\end{pmatrix}+t\begin{pmatrix}1\\0\\1\end{pmatrix}+s\begin{pmatrix}-2\\-2\\-4\end{pmatrix}\space\middle|\space t,s\in\mathbb{R}\right\}


What is the equation of the plane represented by PP?


We want to eliminate tt and ss from the equation.
Since there are 3 total variables and 2 free variables, there will be 1 equation.
Express PP as
(12x102y114z1)\left(\begin{array}{cc|c}1&-2&x-1\\0&-2&y-1\\1&-4&z-1\end{array}\right)
and row reduce
(12x102y114z1)ρ1ρ2+ρ3(12x102y100z1(y1)(x1))\left(\begin{array}{cc|c}1&-2&x-1\\0&-2&y-1\\1&-4&z-1\end{array}\right)\xrightarrow{-\rho_1-\rho_2+\rho_3}\left(\begin{array}{cc|c}1&-2&x-1\\0&-2&y-1\\0&0&z-1-(y-1)-(x-1)\end{array}\right)
The bottom equation has 0=z1(y1)(x1)0=z-1-(y-1)-(x-1), which simplifies to the equation
x+yz1=0x+y-z-1=0
To check notice that all three of the original vectors satisfy this equation.